The Effect of Different Plant Growth Regulators on Shoot Induction of Orthosiphon grandiflorus Boldingh. - Rahmat, Zaidah; Saidali, Mohd. Nazri (2005)
Among herbal plants which had been commercialized recently include Orthosiphon aristatus Boldingh. or better known as Java Tea and â€œmisai kucingâ€. The plantâ€™s leaves are believed to be able to help prevent and eliminate bladder stone apart from some other purposes when used alone or in combination with other plants. The production of the plant using tissue culture technique is hoped to reduce the time for growth under normal cultivation and to produce in a large quantity from a small source of explant. Sources of explant for this study were derived from leaves and stems for comparison. Each of the explants was grown under various plant growth regulators at various concentrations and combinations to determine the best hormone concentration that give adventitious shoots. Explants from stems were found to produce the best overall result with 0.2 mg/L BAP and 0.5 mg/L NAA but at a slower rate. The best result obtained from leaves explants was with 0.2 mg/L BAP which induces shoot faster than stem explants but at a smaller quantity. In comparison to the results from leaves explants, BAP with the same concentration using the stem explants gave a higher number of adventitious shoots. Stems are found to be a better explants source for regeneration of O. aristatus.